Analisis Potensi Pajak Air Tanah dan Kontribusinya Terhadap Penerimaan Pajak Daerah - Fitriani, Fitriani; Yusni, Yusni; Sulistyaningsih, Sulistyaningsih (Amsir Accounting & Finance Journal, 2023)
The implementation of the PDRD Law Number 28 of 2009 concerning the addition and delegation of types of regional taxes and fees has become an opportunity for local governments to maximize all the potential of their regions so that they can increase their regional income. Therefore, exploring the potential and information of groundwater tax in Banggai Regency is one of the important factors to increase local tax revenue. during the 2018-2020 period. This study applies a qualitative descriptive method with a research focus on the potential and contribution of groundwater tax to regional tax revenues in Banggai Regency. The research location is at the Regional Revenue Agency of Banggai Regency. Excavation of the potential for groundwater tax in Banggai Regency resulted in a good percentage in the 2018-2019 period because it had increased and in the 2019-2020 period it had decreased. The untapped potential is 2,641,856,175.4. The biggest groundwater tax contribution is 0.47%, namely in 2019 while in 2018 it was 0.11 and in 2020 it was 0.46. This requires the government's efforts to increase the potential and contribution of groundwater tax so that regional revenues for Banggai Regency also increase.